(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This research addresses the transformations in e-learning and their impact on public relations and media students in the digital age. The study shows special interest in how students receive this type of education and the challenges they face, in addition to the impact of variables such as gender, type of university, and academic level on their attitudes. By analyzing the data collected from students of public and private universities, the results reveal significant differences in acceptance and preferences between different groups, providing valuable signals for developing more effective educational programs that respond to the needs and expectations of this category of students.